Pengaruh Job Satisfaction, Job Resources dan Self Determination Terhadap Work Engagement Karyawan Corry Manurung Grup - Setiawan, Prayoga; Saputro, Arie Hendra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Based on the descriptions above and from several expert opinions, the purpose of this research is to find out how much influence job satisfaction, job resources, and self-determination have on Work Engagement of Corry Manurung Group employees. The method used in this research is a qualitative method with total sampling of all 32 employees of the Corry Manurung Group through filling out a questionnaire in which there are 33 statements. The data that has been collected is then carried out descriptive statistical testing through frequency distribution and hypothesis testing using the Chi-Square method to determine the influence between variables. The results showed that the majority of Corry Manurung Group employees fell into the “good” and “very good” categories on job satisfaction, job resources, selfdetermination, and work engagement variables. Meanwhile, based on the chi-square test using SPSS, only the job satisfaction variable has a significant influence on Work Engagement because it produces a chi-square value <0.05, which is 0.025. The other two variables, namely job resources and self-determination have chi-square values > 0.05, which are 0.057 and 0.135 respectively.